THE CORRELATION BETWEEN EFL LEARNERS’ SELF-CONFIDENCE AND THEIR SPEAKING ACHIEVEMENT - Dea Khoirunnisa; Hamiddin Hamiddin; Eko Suhartoyo (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
AbstractThe aim of this study was to know whether or not there is significance correlation between EFL Learners’ self-confidence and their speaking achievement of the fourth semester students of Engish department at Unisma. The research design in this study is quantitative in the form of correlation design. The subject in this study consists of 30 students. In collecting the data needed to know EFL learners’ self-confidence used questionnaire, adopted from Purba (2014) and collected students speaking achievement by assessing students’ performance in the class. The result showed that r-counted of EFL learners’ self-confidence was .228 with P value .226, level of significant of P value was higher than .05 or .226 > .05. It means that there was no significant correlation between EFL learners’ self-confidence and their speaking achievement. According to the result, it can be said that the null hypothesis is accepted while the alternative hypothesis is rejected.Keywords: correlation, self-confidence, speaking achievement